Burnout and Mental Well-Being in Sports: The Mediating Role of Athlete Engagement and Mental Toughness - Volkan Ozcan, (Journal of Educational Issues, 2024)
The aim of this study is to examine mediating role of athlete engagement and mental toughness in the relationship between burnout and mental well-being. Our theoretical model was tested using data collected from 251 university students (103 females and 148 males) in sports departments aged between 18 and 33 (Mean = 21.73 years, SD = 2.23). Participants completed the Athlete Burnout Questionnaire (ABQ), the Warwick-Edinburgh Mental Well-being Scale (WEMWS), the Athlete Engagement Questionnaire (AEQ), and the Sports Mental Toughness Questionnaire (SMTQ). As a result of multiply mediation analyses showed that a significant total direct effect of burnout on mental well-being, significant direct effect; and a significant indirect effect via athlete engagement, but not a significant indirect effect via mental toughness. Athlete engagement and mental toughness, in combination, did not multiple mediate the association between burnout and mental wellbeing. The possible explanations and future directions are discussed in the light of relevant literature.